Corpo e imagem: uma narrativa de sobrevida nos entremeios da existência - Ribeiro, Henrique Walter (2022)
This poetic research, whose investigative motto thought the threshold between life and death of the body as a matter – as an organic system that presupposes the death and decomposition of any living being – consists of a theoretical-practical study in visual arts that proposes tensions between art and science, life and death, presence and absence, body and image, ephemerality and permanence, all sublimated in a fictional text-visual construction that establishes another narrative by discussing dissolution, the suspension of temporalities with the human body at the end of its biological cycle. For this, the works that underpind this writing were based on methodologies in the field of art research, emphasis on Visual Poetics, having as main practical procedures: the displacement of tools, regular utensils in the areas of health sciences to the artistic field; the construction of situations in which the human body triggers or has triggered these instruments on itself; and, finally, the transformation of this contact into an image; stored from the lenses of the digital camera. As a result of this practice, five imagery paths were conceived whose chaining is structured under the narrative prism of a body being studied. Finally, in order to contribute to the studies and discussions of contemporary art, in the midst of the transit between practice and theory and proposing reinterpretations, rereadings to the times of the body – playing this in the times of the image – reflections were proposed about body, life and image instances.